Epidemiological and Histopathological Profile of Oral and Head-and-Neck Tumors at the National Cancer Institute: A Five-Year Retrospective Analysis (2020–2024) - Ramia Hassan; Madiha Nouralddeen (AlQalam Journal of Medical and Applied Sciences, 2025)
Cancers of the lip and oral cavity rank among the world’s most prevalent malignancies and carry poor survival rates despite therapeutic advances. In Libya, epidemiological data on oral and head‐and‐neck tumors remain limited. This study aimed to characterize the five‐year epidemiological and histopathological profile of these tumors at the National Cancer Institute (NCI), Sabratha, from 2020 to 2024. A retrospective review was conducted of all histologically confirmed carcinomas and sarcomas of the oral cavity, head, and neck recorded in the NCI archives. Patient demographics (age, sex), tumor site, and histopathologic diagnosis were extracted. Data were analyzed using R (v4.0.2) to calculate mean age, gender distribution, site‐specific frequencies, and annual proportions of oral tumors relative to total cancer cases. Among 8,152 cancer cases reported over five years, 48 (0.59%) were oral tumors. Annual oral tumor proportions ranged from 0.34% in 2020 to 0.83% in 2023. The cohort comprised 28 males (58%) and 20 females (42%), with a male-to-female ratio of 1.4:1. The mean patient age was 54.2 years (range: 12–89). The tongue was the most affected site (42.5%), followed by the maxilla (15%) and nasopharynx (12.5%). Squamous cell carcinoma (SCC) constituted 69% of cases, adenocarcinoma 19%, and sarcoma 12%. Among SCCs, 55% occurred in males. Oral and head‐and‐neck tumors comprised less than 1% of all cancers at NCI during 2020–2024, predominantly affecting older males and most frequently involving the tongue as SCC. These findings underscore the need for targeted screening in high‐risk anatomical sites and demographic groups. Future studies should integrate behavioral and environmental risk factors to inform prevention and early‐detection strategies.